Analysis and evaluation of symmetrical key ciphers for internet of things smart home - Lujain S. Abdulla; Musaria K. Mahmood; Abbas F. Salih; Sulaiman M. Karim (Institute of Advanced Engineering and Science, 2021)
A large number of sensors and intelligent devices are interconnected via the internet to collect data as part of the internet of things (IoT) applications. Data security is one of the important challenges for these applications due to vulnerability of the internet. IoT devices limiting factors, such as delay-sensitivity, restricted memory, and low computing capability, make choosing the appropriate data encryption standard extremely important. The current research focuses on evaluating four data security, block cipher standards for the IoT smart home application. Considering the encryption/decryption speed, DES, TDES, AES, and SAFER+ standards are evaluated by implementing the algorithms with MATLAB to determine the best security solution. The simulation of the four standards shows the superiority of SAFER+ standard in term of encryption speed compared to others added to its capabilities on security, and software implementation opportunity. The use of classical symmetric key standards for real time data security in the IoT application can be validated through the selection of SAFER+.